Pendampingan Guru dalam Penggunaan Papan Interaktif Digital sebagai Inovasi Media Pembelajaran - Syafiul Hamidani; Alfiarini Alfiarini; Robi Yanto; Veradilla Amalia; Endang Etriyanti (JURIBMAS : Jurnal Hasil Pengabdian Masyarakat, 2026)
The development of digital technology requires the world of education to continuously adapt to create innovative and interactive learning processes. One learning medium that is starting to be widely developed is the digital interactive board. However, the use of this technology in schools, especially at SD-IT Al-Ikhlas, still faces obstacles, particularly limited teacher competency in operating and integrating it into learning. This community service activity aims to improve teacher competency in using digital interactive boards as an innovative learning medium. The implementation method includes socialization, training, and direct mentoring for partner teachers. The results of the activity show an increase in teacher understanding and skills in operating digital interactive boards and integrating them into the learning process. In addition, teachers have become more creative in developing interactive and engaging learning materials for students. Thus, this mentoring activity is expected to support the improvement of the quality of learning and digital literacy in the school environment